Comparative study between ALVARADO Score and RIPASA Score for the diagnosis of Acute Appendicitis - Karmakar, Prodip Kumar; Debnath, Poly Rani; Farouque, Mohammed Omar; Ali, Md. Showkat; Rahim, Md. Abdur; Kabir, Md. Rezaul (The Planet, 2022)
Background: Several scoring systems have been developed to assist physicians in diagnosing acute appendicitis. The study aimed to compare the ALVARADO score and RIPASA score for the diagnosis of acute appendicitis. Methods & Materials: This comparative study was conducted in Sher-e-Bangla Medical College (SBMC), Barisal, in the Department of Surgery, Unit 1. The study was conducted from 1st January 2021 to 31st December 2021. Data were collected via face-to-face interviews by convenient sampling technique. Informed written consent was taken from the respondents. Data were analyzed by SPSS (Statistical Package for the Social Science) 25 version. Results: Out of 62 respondents, ALVARADO scoring system had Mean ± SD 8.1±1.4, Cut value 8.5, AUC 0.853, Sensitivity 85%, Specificity 73%, PPV (Positive Predictive Value) 48%, NPV (Negative Predictive Value) 94%, Diagnostic accuracy 75%. RIPASA Scoring system had Mean ± SD 11.8±2.1, Cut value 12.75 AUC 0.845, Sensitivity 78%, Specificity 75%, PPV (Positive Predictive Value) 48%, NPV (Negative Predictive Value) 92%, Diagnostic accuracy 76%. Conclusion: Both ALVARADO & RIPASA Scoring system was good for the treatment of acute appendicitis.